2012
DOI: 10.1074/jbc.m112.407189
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Suppresses Telomerase Expression and Human Cancer Growth through MicroRNA-498

Abstract: Background:Telomerase is essential for cancer cell growth. Results: MiR-498 is a novel 1,25(OH) 2 D 3 target gene that decreases telomerase, induces cell death, and suppresses tumor growth. Conclusion: MiR-498 is an important mediator of the anti-tumor activity of 1,25(OH) 2 D 3 . Significance: The studies define a new mechanism of telomerase regulation by small non-coding RNAs in response to 1,25(OH) 2 D 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 57 publications
(42 reference statements)
7
83
0
Order By: Relevance
“…Consistent with these observations a recent experimental investigation has shown that, in ovarian tumor and ovarian cancer cell lines, microRNA-498 (miR-498) induced by 1,25OH 2 D 3 decreased hTERT mRNA expression, fostered cell death, and suppressed tumor growth (Kasiappan et al, 2012). Conversely, the ability of 1,25OH 2 D 3 to decrease hTERT mRNA and to suppress ovarian cancer growth was compromised in the absence of miR-498, following its depletion in cell lines and in tumor-bearing mice (Kasiappan et al, 2012). Finally, Vit D has been reported to foster several types of malignant cells to undergo differentiation toward more mature phenotypes or to induce cell death by triggering apoptosis according to the cell type (Gocek & Studzinski, 2009).…”
Section: Effects Of Vitamin D On Tumor Progressionsupporting
confidence: 59%
See 2 more Smart Citations
“…Consistent with these observations a recent experimental investigation has shown that, in ovarian tumor and ovarian cancer cell lines, microRNA-498 (miR-498) induced by 1,25OH 2 D 3 decreased hTERT mRNA expression, fostered cell death, and suppressed tumor growth (Kasiappan et al, 2012). Conversely, the ability of 1,25OH 2 D 3 to decrease hTERT mRNA and to suppress ovarian cancer growth was compromised in the absence of miR-498, following its depletion in cell lines and in tumor-bearing mice (Kasiappan et al, 2012). Finally, Vit D has been reported to foster several types of malignant cells to undergo differentiation toward more mature phenotypes or to induce cell death by triggering apoptosis according to the cell type (Gocek & Studzinski, 2009).…”
Section: Effects Of Vitamin D On Tumor Progressionsupporting
confidence: 59%
“…On the contrary, VDR overexpression resulted in a potentiation of cell growth arrest (Hedlund et al, 1996;Welsh, 2012;Zhuang et al, 1997). Interestingly, recent studies have shown that 1,25(OH) 2 D 3 may also affect ovarian cancer cells proliferation by decreasing human telomerase reverse transcriptase (hTERT) mRNA through a small non-coding RNA (Ikeda et al, 2003;Kasiappan et al, 2012). Consistent with these observations a recent experimental investigation has shown that, in ovarian tumor and ovarian cancer cell lines, microRNA-498 (miR-498) induced by 1,25OH 2 D 3 decreased hTERT mRNA expression, fostered cell death, and suppressed tumor growth (Kasiappan et al, 2012).…”
Section: Effects Of Vitamin D On Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor activity of 1,25(OH) 2 D 3 can be mediated by microRNA specific for the telomerase transcript in OC and in other human cancer types (29). It has been demonstrated that 1,25(OH) 2 D 3 also inhibits proliferation of adrenocortical and pancreatic cancer cells and suppresses hepatocellular carcinoma development by reducing inflammatory cytokine production in vivo (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis of cancer cell lines indicated substantially reduced expression of miR-498 (Kasiappan et al, 2012). Therefore it will be interesting to note if miR-498 reconstitution will be helpful in suppressing ovarian cancer.…”
Section: Tumor Suppressormentioning
confidence: 99%